Education on Business Partnerships for Corporate Sustainability at Kristoforus 2 in West Jakarta - Chelsya Chelsya (Advances in Community Services Research, 2026)
Purpose: This Community Service Activity (PKM) aims to enhance students’ understanding of the concepts, benefits, and implementation of business combinations as a strategy for corporate growth and sustainability. The program was launched because students’ understanding of business combination practices—which are widely applied in the business world—remains limited. Method: The event was held in person on April 13, 2026, at SMA Kristoforus 2 in West Jakarta, with 31 eleventh-grade students participating. The methods used included educational sessions, case-study-based discussions, pre- and post-tests administered via Quizizz, and a participant satisfaction survey. Results and Discussion: Before the activity, most participants did not yet understand the concept of business combinations. Following the intervention, understanding increased, as evidenced by an average post-test score of 84. Participants showed great enthusiasm during the educational sessions and discussions. The outcomes of the activity included journal articles, intellectual property rights (IPR), and educational materials, including posters. Implications: This program helps improve students’ business literacy and supports economics education in schools. Similar activities should be developed on an ongoing basis, with a greater focus on practical economic and financial topics.